The relationship between principals' transformational leadership practices and teachers' motivation in selected Islamic private schools in Songkhla, Southern Thailand. - Wanlabeh, Natyada (Institute of Education, International Islamic University Malaysia, 2011)
The purpose of this study is to examine the relationship between principals' transformational leadership and teachers' motivation as perceived by teachers in the context of Islamic private schools in Songkhla, Southern Thailand. This study also investigates whether teachers' demographic characteristics such as age, gender, marital status, and years of teaching experience, impact their perceptions toward principals' transformational leadership practices. The study uses survey questionnaire to collect data and analyzes the data using descriptive statistics, regression analysis, and one way ANOVA. The respondents are 174 teachers from six selected Islamic private schools in Songkhla. The findings indicate that teachers perceive their principals exhibited transformational leadership more frequently than transactional leadership. Idealized influence (IIB & IIA) and inspirational motivation (IM) are found to be the greatest leadership practices among the principals, and individual consideration (IC) and intellectual stimulation (IS) are rated lowest among transformational leadership aspects. The results of the regression analysis indicate that teachers' motivation is significantly related to principals' transformational leadership practices. The findings demonstrate that individual consideration factor (IC) highly affect all dimensions of teachers' motivation, including attitude towards work, commitment/effort, challenge, and professional development; inspirational motivation behaviour (IM) impact on increasing teachers' positive attitude towards work, commitment or effort to teach, and challenge, and the idealized influence (IIA and IIB) are relative to teachers' attitude towards teaching, effort or commitment, and professional development. However, no significant relationship between principals' intellectual stimulation (IS) factor and teachers' motivation is found in this study. The findings from one way ANOVA reveal gender, marital status, and age of teachers effect their perceptions toward the principals' transformational leadership practices. Single, female teachers aged between 30 to 45 years old view principals displaying more transformational leadership than do the other groups. Based on these findings, implications are that current emphasis on transformational leadership for school effectiveness, improving teachers' motivation and increasing students' achievement are moving toward the right direction, which authorities should give more support, especially to intellectual stimulation and individual consideration aspects of principals.